Advancing health equity through a theoretically critical implementation science. Issue 8 (27th April 2021) - Snell-Rood, Claire; Jaramillo, Elise Trott; Hamilton, Alison B; Raskin, Sarah E; Nicosia, Francesca M; Willging, Cathleen
Abstract: While implementation science is driven by theory, most implementation science theories, models, and frameworks (TMF) do not address issues of power, inequality, and reflexivity that are pivotal to achieving health equity. Theories used in anthropology address these issues effectively and could complement prevailing implementation science theories and constructs. We propose three broad areas of theory that complement and extend existing TMF in implementation science to advance health equity. First, theories of postcoloniality and reflexivity foreground attention to the role of power in knowledge production and to the ways that researchers and interventionists may perpetuate the inequalities shaping health. Second, theories of structural violence and intersectionality can help us to better understand the unequal burden of health disparities in the population, thereby encouraging researchers to think beyond single interventions to initiate partnerships that can impact overlapping health vulnerabilities and influence the upstream causes of vulnerability. Finally, theories of policy and governance encourage us to examine the social-political forces of the "outer context" crucial for implementation and sustainability. The incorporation of critical theories could enhance implementation science and foster necessary reflexivity among implementation scientists. We contend that a theoretically critical implementation science will promote better science and, more importantly, support progress toward health equity.